The demography of Balanites maughamii : an elephant-dispersed tree - Bijl, Alison (Department of Biological Sciences, 2017)
Balanites maughamii is an ecologically and culturally valuable tree species, heavily impacted by elephants, which strip bark selectively off the largest trees, increasing their susceptibility to fire damage. Elephants also break intermediate sized trees extensively, keeping them trapped in non-reproductive stages. The trees can however survive breaking, stripping and · toppling by elephants, as well as top kill by fires, because they resprout vigorously in response to damage. They also produce root suckers. independently of disturbance. Vegetative reproduction buffers the populations from the infrequent recruitment of seedlings, and facilitates the maintenance of populations over the short term. Balanites maughamii trees are reliant on African elephants (Loxodonta africana) for seed dispersal and to provide a germination cue through mastication. In the absence of elephants, the population experiences a recruitment bottleneck, but root suckers functionally replace seedlings and fill the "recruitment gap", so over the short term, the population is resilient. In all populations, whether elephants are present or not, another hurdle affects recruitment, and it is seed limitation due to seed predation pre- and post- dispersal. Cafeteria experiments revealed that bushveld gerbils (Tatera leucogaster) were removing many seeds but do not scatter- or larder-hoard. They are simply seed predators.